How To Development of Pop Up Book Media To Improve Literacy In Tsunami Disaster Mitigation For Elementary School Students? - Yoga Marga Mahendra; Risky Dwi Cahya; Herwin (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to create a Pop Up book about disasters and assess how good and useful it is as a learning tool. This type of research is Research and Development (R&D), using a five-stage ADDIE development model, namely analysis, design, development, implementation, and evaluation.Â  The method used in this study used interview methods, questionnaires. The data collection instruments used are questionnaire sheets, and multiple choice tests. The validation assessments for the Pop Up Book media involved experts, with the media expert assessment at 69.4, considered "Good." Material validators rated it 88.8, classifying it as "Excellent." The assessment by learners and language validators scored 82.1 and 90 respectively, both falling into the "Excellent" category. Additionally, the grade 3 homeroom teacher's questionnaire scored 88.6, while the principal's assessment reached 86.3, both categorized as "Excellent." The pre-test average was 51.6, increasing to 80.3 in the posttest. Soit can be concluded that the Pop Up Book media for tsunami disaster mitigation is suitable for use in learning in elementary schools